Field Experiments on Load-Settlement Behaviors of Lightweight Foamed Soft Ground - Yea, Geu Guwen; Yoon, Gil Lim; Kim, Sun Bin; Kim, Hong Yeon (KSCE journal of civil engineering, 2022)
In the construction of relatively light structures, lightweight foamed soil (LWFS) has been widely applied in soft foundation replacement for controlling the strength and unit weight of soft grounds, because deep ground improvement over the entire soft layer can be costly and time consuming. In this study, the stress-settlement behavior according to the replacement thickness was analyzed through a plate load test using bearing plates of various diameters on a soft ground replaced with an LWFS. Consequently, the bearing capacity increases as the plate diameter decreases. At a replacement thickness of 0.5 m, the final load applied to a plate with a diameter of 1,000 mm was reduced by 38% compared with that applied to a plate with a diameter of 300 mm, whereas the settlement increased by approximately 85%. When the replacement thickness was 1.5 m, in the test on a plate with a diameter of 300 mm, the final load increased by approximately 153% compared to that of the replacement thickness of 0.5 m. In addition, the settlement was 158% larger than that of the replacement thickness of 0.5 m. Consequently, the load to reach the same settlement increased with an increasing replaced depth.